Battery-assisted charging system for simultaneous charging of electric vehicles. (1st April 2016) - Aziz, Muhammad; Oda, Takuya; Ito, Masakazu
Abstract: A battery-assisted charging system has been developed to improve the charging performance of a quick charger for electric vehicles. The developed system mainly consists of an alternating current-to-direct current inverter, a direct current-to-direct current voltage converter, a stationary battery, and an electric vehicle charger. The difference in charging rates in different seasons (winter and summer) was determined initially to measure the effect of electric vehicle battery temperature (influenced by surrounding temperature) on the charging rate. The charging rate during summer was higher than that during winter. In addition, simultaneous charging experiments were performed in different seasons (winter and summer) and for different contracted power capacities (50, 30, and 15 kW). Compared to a conventional charging system, the developed system can improve the charging performance of electric vehicle chargers in terms of the charging rate, while maintaining the contracted power capacity. Highlights: Battery-assisted charging system for electric vehicles has been proposed. Simultaneous charging experiments were performed. Charging behaviors in winter and summer were clarified. Charging performance has been improved significantly during simultaneous charging.